The Real Convergence of CEE Countries: A Study of Real GDP per capita - Andrea Zarembova; Stefan Lyocsa; Eduard Baumöhl (Ekonomicky časopis/Journal of Economics, 2012)
The paper examines the unconditional sigma and time-series convergence of real GDP per capita (measured in national currencies and euros) for CEE8 countries during the 1995 : Q1 – 2011 : Q1 period by applying the unit root fra-mework using the DF-GLS test and the Lee and Strazicich (2003; 2004) test, which allows for endogenous breaks in trends and constants. We selected Germany as a benchmark country for relative real GDP per capita because of its geographical and economical position relative to all CEE8 countries. We have found that both sigma convergence and time-series convergence were present for most of the CEE8 countries prior to the breaks in trends, but after the breaks, the convergence slowed or reversed and thus indicated divergence.
Keywords: C22; G01; E0; O40; P20; 330; time-series convergence; sigma convergence; CEE; unit root test; structural breaks